Reconstruction of Hominid Phylogeny on the Basis of Cladistic Analysis - Kaszycka, Katarzyna A. (Anthropological Review, 1993)
Phylogenetic relationships among eight hominid taxa (the Australopithecines and Homo) are examined using cladistic techniques. Data on morphological and morphometric characters of fossil hominid crania, mandibles and dentition were collected from the literature. Cladograms were constructed using the PAUP phylogeny program to find the best fitting (maximum parsimony) hypotheses. Two equally the most parsimonious cladograms were found. The genus Homo is confirmed to be monophyletic, while Australopithecus is not. Results of this analysis support a close phylogenetic relationship of A.africanus to both Homo and the "robust” Australopithecine clades. Even though the relationships of A.aethiopicus (WT17000) are ambiguous, the most parsimonious cladograms do not place this species as a sister taxon of both A.boisei and A.robustus.